Business Cycle in China since the Lehman Crisis: Interaction among Macroeconomic Policy, Economic Growth and Inflation. (22nd September 2013) - Kwan, C. H.
Abstract: The major objectives of China's macroeconomic policy are to stabilize economic growth and inflation, which, in turn, are important factors determining key prices, such as the policy interest rate, the renminbi exchange rate and stock prices. In a framework that distinguishes different phases of the business cycle based on whether the current period's economic growth rate and inflation rate are above or below their "normal" values, this paper analyzes the interaction among macroeconomic policy, economic growth and inflation in China since the Lehman crisis, and the implications for these key prices. The path of China's economy indicates that stimulus measures taken by the government during the recession phase and tightening measures implemented during the overheating phase have helped minimize the fluctuation over the business cycle. Our analysis shows that Chinese authorities tend to rely more on adjusting the exchange rate than the interest rate to stabilize the economy. Comparing with conditions at the time of the post‐Lehman recession, the current slow pace of economic growth in China may reflect not only weakening demand, but also a lower potential growth rate associated with the arrival of the Lewis turning point.